FAKTOR MENURUNNYA EKSPOR KEPITING INDONESIA KE AMERIKA SERIKAT - Lastri "; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research aims to study and discuss about factors that led crab exports from Indonesia to United State of America declined. Crab exports from Indonesia to United State of America were expected could give big contribution for foreign exchange and tighten Indonesian economic relation between Indonesia and United State of America. Some of the factors that led to exports decline of crab from Indonesia to U.S come from the internal and the external factors.This study uses analysis level of the stated that focus on crab exports from Indonesia to U.S decrease factors. This study also uses liberal perfective and international trade theory from Ricardo and Porter. Crab exports that experience obstacles from U.S made Indonesia had to fix their system. This case caused Indonesian marine sector decreasing.Crab exports from Indonesia to U.S experienced decreasing almost every year, especially in 2009. The external factors are the crisis that happened in U.S and the refusal to Indonesian fishery products, particularly the crabs. The internal factors are lack of attention from the government for crab cultivation development. Indonesia still rely on the catch of fisherman. The other internal factor is there are exploitations to the crab spawn.Keywords: crab exports, obstacles, internal factors, external factors, USFDA refusal,economic